The strategy pyramid: strategic marketing analysis for developing countries - Andaleeb, Syed Saad; Gardner, David M. (© 1990 The Haworth Press, Inc., 2016)
This article was published in the Journal of Global Marketing [© 1990 by The Haworth Press, Inc.] and the definite version is available at : http://dx.doi.org/10.1300/J042v03n01_01 The Journal's website is at: http://www.tandfonline.com/doi/abs/10.1300/J042v03n01_01?journalCode=wglo20